2021
DOI: 10.1108/wje-03-2021-0162
|View full text |Cite
|
Sign up to set email alerts
|

Invention of sustainable geopolymer concrete made with low calcium waste wood ash

Abstract: Purpose Inefficient waste disposal technique and cement production methodology caused significant environmental impacts, leading to global warming. The purpose of the research was to invent an effective, sustainable technology to use the wastes and alternate for cement in concrete. Geopolymer technology could be the most desirable solution to use the wastes into an effective product. Design/methodology/approach The wood waste ash derived from nearby tea shops was used as an alternate binder for fly ash. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The findings showed that incorporating rubber fibre up to 1 % achieved the maximum increment rate compared to other mixes. Hence, the rubber fibre improved the tensile and flexural strength of GPC [37,42].…”
Section: Fig 5 a Influence Of Rubber Fibre In Compressive Strengthmentioning
confidence: 91%
See 1 more Smart Citation
“…The findings showed that incorporating rubber fibre up to 1 % achieved the maximum increment rate compared to other mixes. Hence, the rubber fibre improved the tensile and flexural strength of GPC [37,42].…”
Section: Fig 5 a Influence Of Rubber Fibre In Compressive Strengthmentioning
confidence: 91%
“…Hence, disposal of that waste rubber tire was a challenging task for the cleaner environment. Awareness on utilizing waste rubber tires in concrete composites was increased, and it was used as a filler material and coarse aggregate [37]. Crumped rubber was replaced by 15percent with fine aggregate, which enhanced better performance; however, it reduces the compressive strength [36].…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, an examination was conducted to create high-performance concrete (HPC) by substituting various percentages of alccofine (5,10,15,20,25, and 30%) for cement and glass powder (10, 20, 30, 40 and 50%) for fine aggregate. The results of the fresh and mechanical index tests conducted on all concrete mixtures are highlighted in the current study.…”
Section: Objectivesmentioning
confidence: 99%
“…As a result, utilising SCM as a partial or alternative to cement can lower the amount of cement used in the production of concrete and lower environmental pollution [6][7][8][9]. SCM comes in a variety of forms, including Ultra-fine Palm Oil Fuel Ash (UPOFA) [10], Waste Bottom Ash (WBA) [11], Calcined Clay [12], Rice Husk Ash (RHA) [13], Metakaolin [14], Fly Ash (FA) [15], Limestone Powder (LP) [16], Ground Granulated Blast furnace Slag (GGBS) [17], Glass Powder (GP) [18,19], Bio-Medical Waste Ash (BWA) [20][21][22][23][24], Waste Wood Ash (WWA) [25][26][27] and E-Waste [28,29]. The waste materials released from factories and industry is processed to produce the SCM.…”
Section: Introductionmentioning
confidence: 99%
“…Plenty of research works focus on the utilization of flyash for the development of geopolymer concrete [6][7][8], bio medical waste ash [9,10], wood ash [11][12][13][14][15], GGBS [16][17][18]. Low calcium fly ash is widely preferred owing to its abundance availability and cheap cost.…”
Section: Introductionmentioning
confidence: 99%